MATLAB GUI Application for Processing the Remote Sensing Images - Andriani Putri; Shou-Hao Chiang; Abdurrahman Ridho (Universitas Teuku Umar, 2023)
Spatial Data Analyst is important for image processing and accuracy assessment. To adjust a better image, we need to do some processes and steps in order to achieve this goal. MATLAB has been commonly used in image processing. MATLAB provides a Graphical Use Interface (GUI) designer